Investing Muslim public funds for fulfilling maqasid al-shari'ah: a case study of tabung masjid in malaysia - Zakariyah, Luqman; Sarif, Suhaimi Mhd; Ahmad H.Osman, Rahmah; Abdul Rahman, Shukran; Mohd Noor, Azman (International Islamic University Malaysia, 2017)
This study aims at determining the investment strategies of Masjids in Malaysia. Drawing from the success story of Tabung Haj, the study has focused on establishing the need for the efficiency in investing Tabung Masjid toward benefiting the public and fulfilling maqāÎid al-SharÊÑah (Objectives of SharÊÑah). The study introduces a MaqÉÎid based framework to test the significance of investing TM. The sample consists of 287 mosques in 9 states of Malaysia. Cross-tabulation, ANOVA, and correlations were conducted on the data collected through self-administered questionnaire. Granger causality test is performed on the forecasted investment and development indicators. Cross-tabulation results indicated that amount of donations and investment strategies of tabung vary states in Malaysia. ANOVA results have proved that money saved by mosques in banks varies significantly among states. Tukey test results indicate that mosques in southern states save less amount of Tabung Masjid in the bank compared to the masjid in other states. Correlation results proved that savings in the bank have a negative relationship with the intention toward general and capital investment. Investment of Tabung Masjid is found to have a significant positive causal relationship with economic development. Data used for analysis is of opinion and forecasted values, the exact amount of donation and investment in various sources could not be obtained. Efficient utilization of Tabung Masjid will allow mosques to play a significant role in shaping the socio-economic profile of Muslim community in Malaysia and similar initiative will also be helpful for any developing countries.